A method for improving wettability and bonding between aramid fiber and epoxy resin

By sonicating and chemical sizing the aramid fiber or aramid fabric at high temperature solution, the problem of insufficient wetting and adhesion with epoxy resin is solved, and the performance of the composite material is significantly improved.

CN115748231BActive Publication Date: 2025-02-28SINOCHEM HIGH PERFORMANCE FIBER MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211473786.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-02-28
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The poor wetting and adhesion of aramid fibers and epoxy resins limits their application in the field of composite materials.

Method used

The two-step method is used to treat aramid fibers or aramid fabrics. The surface oil agent is first removed by sonication of the high-temperature solution, and then chemically treated with a sizing agent containing isophthalyzedyl isocyanate-type thermally tough polyurethane and coupling agent to enhance the active site on the fiber surface.

Benefits of technology

The wetting and adhesion between aramid fiber and epoxy resin is significantly improved, the wetting time is shortened, and the interlayer shear strength and bending load of the composite material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004999627580000091
    Figure GDA0004999627580000091
  • Figure GDA0004999627580000102
    Figure GDA0004999627580000102
  • Figure GDA0004999627580000141
    Figure GDA0004999627580000141
Patent Text Reader

Abstract

The present invention provides a method for improving the wettability and / or adhesion of aramid fiber or aramid fabric with epoxy resin or a method for treating aramid fiber or aramid fabric, the method comprising the following steps: (1) physical treatment, comprising sequentially subjecting the aramid fiber or aramid fabric to high temperature solution ultrasonic treatment and ethanol ultrasonic treatment; (2) chemical treatment, comprising sizing the aramid fiber or aramid fabric after the physical treatment with a sizing agent, wherein the sizing agent comprises meta-phenylenedimethyl isocyanate type thermo-tough polyurethane and a coupling agent. The method of the present invention shortens the wetting time of the aramid fiber or aramid fabric with epoxy resin, and improves the interlaminar shear strength and bending load of the aramid epoxy resin composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-performance fiber composite materials and relates to a method for improving the wettability and adhesion between aramid fiber and epoxy resin. Background Art

[0002] Para-aramid fiber has many excellent properties such as high specific strength, high specific modulus, chemical resistance, heat resistance and high dimensional stability. However, para-aramid is a rigid benzene ring structure, and the benzene ring has a strong shielding effect and steric effect on the hydrogen atoms on the amide bond -CONH-, resulting in a lack of sufficient active sites in the molecular structure of para-aramid, which is manifested in poor wettability and weak adhesion in the macroscopic sense, thus severely limiting the application of para-aramid in the field of composite materials.

[0003] The molding of aramid fiber / epoxy resin composite materials must fully solve the wettability problem of aramid, so the surface of aramid fiber needs to be modified. The existing technology for aramid surface modification is divided into chemical modification and physical modification. The chemical method includes surface grafting, surface etching, coupling agent modification, etc., and the physical method includes co-condensation, plasma, surface coating, high-energy ray, ultrasonic impregnation, etc. The physical method focuses on increasing the roughness of the fiber surface, while the chemical method introduces functional groups on the fiber surface. However, the existing aramid surface modification methods have the disadvantages of complex operation, high equipment requirements, and certain damage to the fiber.

[0004] The production of aramid fiber / epoxy resin composite materials not only needs to solve the problem of aramid fiber wettability, but also needs to solve the problem of its industrialization and industrialization implementation, that is, the operability of large-scale processing. The existing aramid surface modification methods not only have high requirements on processing equipment, but also have complex process, long processing time, great damage to the fiber, and ultimately increase the cost, and are extremely unfavorable to industrialization.

[0005] In composite materials, fibers are used as reinforcements in different forms such as woven fabrics, warp knitted fabrics or unidirectional non-woven fabrics. The processability of fibers is also one of the important factors affecting the performance of composite materials. Aramid fibers are oiled in the last step of the production process to increase the bundling of the fibers and facilitate further weaving of the fibers. The existing technologies are basically treatment technologies for aramid fibers themselves, which will cause certain damage to the fibers and are not conducive to the next step of processing the fibers into fabrics. The surface of fibers treated by existing physical methods becomes rough and the oil agent is eliminated or distributed unevenly, which will lead to different degrees of wear after fiber processing, and instead cause local defects. Fibers treated by existing chemical methods may lose powder due to friction during the weaving process, which will affect the effect of the treatment. Summary of the invention

[0006] The present invention mainly solves the problem of poor wettability and poor adhesion between aramid fiber and epoxy resin. The present invention provides a process method for improving the wettability and / or adhesion between aramid fiber or aramid fabric (especially aramid fabric, such as aramid woven fabric) and epoxy resin, especially a new type of pre-treatment method for aramid fiber or aramid fabric, which shortens the wetting time of aramid fiber or aramid fabric and epoxy resin, and improves the interlaminar shear strength and bending load of aramid fiber / epoxy resin composite materials. The aramid fiber or aramid fabric treated by the method of the present invention is suitable for aramid epoxy resin composite materials, especially for lithium battery assembly (PACK) battery box composite materials.

[0007] Specifically, one aspect of the present invention provides a method for improving the wettability and / or adhesion of aramid fiber or aramid fabric with epoxy resin or a method for treating aramid fiber or aramid fabric, the method comprising the following steps:

[0008] (1) physical treatment, comprising sequentially subjecting the aramid fiber or aramid fabric to high temperature solution ultrasonic treatment and ethanol ultrasonic treatment, wherein the high temperature solution ultrasonic treatment comprises ultrasonic treatment at a temperature above 60° C. using a washing solution, wherein the washing solution comprises sodium dodecylbenzene sulfonate and sodium fatty alcohol ether sulfate;

[0009] (2) Chemical treatment, comprising sizing the aramid fiber or aramid fabric after physical treatment with a sizing agent, wherein the sizing agent comprises meta-xylylene diisocyanate type thermoplastic polyurethane and an optional coupling agent.

[0010] In one or more embodiments, the sizing agent comprises meta-xylylene diisocyanate type thermally flexible polyurethane and a terminal epoxy polyether type silicone coupling agent.

[0011] In one or more embodiments, in the washing solution, the content of sodium dodecylbenzene sulfonate is 5-15 wt %, and the content of sodium fatty alcohol ether sulfate is 5-15 wt %.

[0012] In one or more embodiments, the pH of the wash solution is 8-9.

[0013] In one or more embodiments, in the ultrasonic treatment of the high temperature solution, the ultrasonic temperature is 70-90° C., the ultrasonic frequency is 60-100 KHz, and the ultrasonic time is 20-40 min.

[0014] In one or more embodiments, after the high temperature solution is ultrasonically treated, the aramid fiber or aramid fabric is dried and then ultrasonically treated with ethanol.

[0015] In one or more embodiments, in the ethanol ultrasonic treatment, the ultrasonic temperature is 20-30° C., the ultrasonic frequency is 40-70 KHz, and the ultrasonic time is 8-12 min.

[0016] In one or more embodiments, after the ethanol ultrasonic treatment, the aramid fiber or aramid fabric is dried and then subjected to chemical treatment.

[0017] In one or more embodiments, after the physical treatment, the weight change rate of the aramid fiber or aramid fabric is ≥5wt%, preferably 5wt%-6wt%.

[0018] In one or more embodiments, the aramid fabric is aramid woven fabric, aramid knitted fabric or aramid nonwoven fabric.

[0019] In one or more embodiments, the meta-xylylene isocyanate-based heat-tough polyurethane is a meta-xylylene isocyanate-based heat-tough polyurethane contained in one or more meta-xylylene isocyanate-based heat-tough polyurethane emulsions selected from Sancure 1601, Sancure 2026C and Sancure 20066.

[0020] In one or more embodiments, the coupling agent is selected from one or more of an aziridine crosslinking agent and an epoxy-terminated polyether-type silicone coupling agent, wherein the aziridine crosslinking agent is preferably CX100, and the epoxy-terminated polyether-type silicone coupling agent is preferably glycidyloxypropyltrimethoxysilane and / or glycidyloxypropyltriethoxysilane.

[0021] In one or more embodiments, the sizing agent comprises an epoxy-terminated polyether-type silicone coupling agent, and the epoxy-terminated polyether-type silicone coupling agent is preferably glycidyloxypropyltrimethoxysilane and / or glycidyloxypropyltriethoxysilane.

[0022] In one or more embodiments, the sizing agent comprises an aziridine crosslinker, and the aziridine crosslinker is preferably CX100.

[0023] In one or more embodiments, the content of the isocyanate-based heat-resistant polyurethane in the sizing agent is 2wt%-6wt%. When the sizing agent contains the coupling agent, the mass of the coupling agent in the sizing agent is preferably 2.5-25% of the mass of the isocyanate-based heat-resistant polyurethane.

[0024] In one or more embodiments, the mass of the epoxy-terminated polyether-type silicone coupling agent in the sizing agent is 2.5-25% of the mass of the meta-xylylene isocyanate-type thermally tough polyurethane.

[0025] In one or more embodiments, the sizing agent is prepared using isocyanate-based thermo-tough polyurethane emulsion, the solid content of the isocyanate-based thermo-tough polyurethane emulsion is preferably 40±5%, the viscosity at room temperature is preferably 60±10cps, the pH is preferably 7.5±0.5, and the surface tension is preferably 46.7±5dynes / cm; the isocyanate-based thermo-tough polyurethane emulsion is preferably selected from one or more of Sancure1601, Sancure2026C and Sancure20066; preferably, the content of the isocyanate-based thermo-tough polyurethane emulsion in the sizing agent is 5wt%-15wt%, and when the sizing agent contains the coupling agent, the mass of the coupling agent in the sizing agent is preferably 1-10% of the mass of the isocyanate-based thermo-tough polyurethane emulsion.

[0026] In one or more embodiments, the mass of the epoxy-terminated polyether-type silicone coupling agent in the sizing agent is 1-10% of the mass of the meta-xylylene isocyanate-based thermally tough polyurethane emulsion.

[0027] In one or more embodiments, in step (2), sizing is performed using a vacuum assisted resin introduction process.

[0028] In one or more embodiments, in the chemical treatment, drying is performed after sizing is completed, and / or the sizing rate is controlled to be 1-5wt%, preferably 1-3wt%.

[0029] Another aspect of the present invention provides an aramid fiber or an aramid fabric, wherein the surface of the aramid fiber or the aramid fabric is free of oil agent and is bonded with meta-xylylene diisocyanate type thermal toughness polyurethane and an optional coupling agent.

[0030] In one or more embodiments, the aramid fiber or aramid fabric is prepared by the method described in any embodiment of the present invention.

[0031] Another aspect of the present invention provides an aramid-epoxy resin composite material, wherein the aramid-epoxy resin composite material comprises the aramid fiber or aramid fabric described in any embodiment of the present invention and an epoxy resin.

[0032] In one or more embodiments, the aramid epoxy resin composite material is an aramid epoxy resin laminate; preferably, the aramid epoxy resin laminate comprises 5-50 layers of aramid fabric, such as 10 layers, 20 layers, 30 layers, 40 layers, and the mass fraction of epoxy resin in the aramid epoxy resin laminate is 20%-50%.

[0033] Another aspect of the present invention provides a battery box or a lower box of a battery box of a lithium ion battery or a lithium ion battery pack, wherein the battery box or the lower box of the battery box comprises the aramid epoxy resin composite material described in any embodiment of the present invention. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0035] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0036] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0037] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0038] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0039] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0040] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0041] The present invention uses a two-step method to process aramid fibers or aramid fabrics (especially aramid fabrics, such as aramid woven fabrics). The first step is to use a physical method to pre-treat the aramid to remove oil, and the second step is to use a chemical method to pre-coat the aramid with sizing. The present invention uses a sizing agent containing meta-phenylenedimethyl isocyanate-type thermally tough polyurethane and an optional coupling agent for the first time in the chemical method to perform "grafting" aramid sizing. The -NCO group on the benzene ring of the meta-phenylenedimethyl isocyanate-type thermally tough polyurethane can form a hydrogen bond with the -NHCO- group of the aramid fiber, and both the aramid and this type of polyurethane contain rigid benzene rings. The two interact with each other, so that the electron cloud density on the benzene ring increases, forming a stable structure similar to π-π conjugation, greatly increasing the affinity effect between the meta-phenylenedimethyl isocyanate-type thermally tough polyurethane and the aramid fiber, forming the first "grafting". Preferably, the sizing agent also contains an epoxy-terminated polyether-type silicone coupling agent, which serves as the second "grafting" between the polyurethane and the epoxy resin. The epoxy-terminated polyether-type silicone coupling agent with an -O- group enhances the flexibility and compatibility of the aramid fiber / epoxy resin system, and the epoxy-terminated group also enhances the affinity with the epoxy resin. The physical treatment step and the chemical treatment step in the method of the present invention achieve the technical effect of "1+1>2", improve the wettability of the aramid fiber and the epoxy resin, and greatly improve the interlaminar shear strength of the processed aramid fiber / epoxy resin composite laminate, which completely solves the problem of poor adhesion of the aramid fiber, and the treatment method is simple, easy and efficient.

[0042] The method of improving the adhesion and / or wettability of aramid fiber or aramid fabric with epoxy resin of the present invention comprises firstly subjecting the aramid fiber or aramid fabric to physical treatment and then subjecting the aramid fiber or aramid fabric to chemical treatment. In the present invention, fabric refers to a flat soft piece of material formed by fibers being crossed, entangled or connected, including woven fabrics formed by fibers having a crossing relationship, knitted fabrics formed by fibers having a entangled relationship, and non-woven fabrics (non-woven fabrics, such as unidirectional fabrics) formed by fibers having a connected relationship. In the present invention, the treatment object is preferably aramid fabric, in particular aramid woven fabric. The present invention is particularly effective in improving the adhesion and / or wettability of aramid fabrics, such as aramid woven fabrics, with epoxy resin.

[0043] The method of the invention is particularly suitable for treating para-aramid (ie poly(p-phenylene terephthalamide)) fiber or para-aramid fabric, and can significantly improve the wettability and bonding property of the para-aramid fiber or para-aramid fabric with epoxy resin.

[0044] In the present invention, the physical treatment includes high-temperature solution ultrasonic treatment (ultrasonication of aramid fiber or aramid fabric in a washing solution at high temperature for a period of time) and ethanol ultrasonic treatment (ultrasonication of aramid fiber or aramid fabric in ethanol for a period of time), the purpose of which is to clean the oil on the surface of the aramid fiber and reduce the damage to the fiber.

[0045] In the present invention, the chemical treatment includes using a solution containing meta-phenylenedimethyl isocyanate type heat-tough polyurethane and a terminal epoxy polyether type silicone coupling agent as a sizing agent to sizing the aramid fiber or aramid fabric, the purpose of which is to increase the chemical bonding sites between the surface of the aramid fiber and the epoxy resin, improve the wettability of the epoxy resin to the aramid fiber, and thus fundamentally improve the adhesion between the aramid fiber and the epoxy resin. The present invention finds that there is a synergistic effect between the meta-phenylenedimethyl isocyanate type heat-tough polyurethane and the terminal epoxy polyether type silicone coupling agent in improving the wettability and adhesion of the epoxy resin to the aramid fiber, and the two can be used together to exert the best improvement effect.

[0046] In the present invention, the aramid fiber or aramid fabric treated by physical and chemical methods and epoxy resin can be prepared into a composite profile by using vacuum bag hot pressing technology and other processes. Before processing, the aramid fiber or aramid fabric can be cut as needed.

[0047] In the present invention, the fineness of the aramid fiber can be 500D-5000D, such as 800D, 1000D, 1200D, 1500D, 3000D. The tensile strength of the aramid fiber is preferably greater than 19cN / dtex, and the elongation is preferably 3.5±0.2%. Examples of aramid fibers include SF2800 and SF6800 of medium-high fiber. The surface density of the aramid fabric suitable for the present invention, such as aramid woven fabric, is preferably 150-460g / m 2 , for example 200g / m 2 , 220g / m 2 , 250g / m 2 , 300g / m 2 , 350g / m 2 , 400g / m 2 In some embodiments, the processing object of the present invention is aramid woven fabric made of 1000D aramid filament as raw material, wherein the surface density of the aramid woven fabric is 150-460g / m 2 , preferably 195-255g / m 2 , more preferably 220g / m 2 .

[0048] In the present invention, the washing solution used for the high-temperature solution ultrasonic treatment is an aqueous solution containing or only containing sodium dodecylbenzene sulfonate and sodium fatty alcohol ether sulfate. The content of sodium dodecylbenzene sulfonate in the washing solution is preferably 5-15wt%, such as 8wt%, 10wt%, 12wt%. The content of sodium fatty alcohol ether sulfate in the washing solution is preferably 5-15wt%, such as 8wt%, 10wt%, 12wt%. The pH of the washing solution is preferably 8-9, such as 8.5. Ammonia water can be used to adjust the pH of the washing solution. In the high-temperature solution ultrasonic treatment, the solution temperature is above 60°C, such as 60-100°C, preferably 70-90°C, such as 80°C, the ultrasonic frequency is 60-100KHz, preferably 80±10KHz, and the treatment time is 20-40min, such as 30±5min. After the high-temperature solution ultrasonic treatment, the aramid fiber or aramid fabric is dried, the temperature can be 110-130°C, such as 120°C, and the time can be 25-35min, such as 30min.

[0049] After the high temperature solution ultrasonic treatment is completed, the aramid fiber or aramid fabric is subjected to ethanol ultrasonic treatment using anhydrous ethanol. During the ethanol ultrasonic treatment, the ultrasonic frequency can be 40-70KHz, preferably 50±5KHz, and the treatment time can be 8-12min, such as 10±1min. No heating is required during the ethanol ultrasonic treatment, and it can be carried out at 20-30°C, such as room temperature (25°C). After the ethanol ultrasonic treatment, the aramid fiber or aramid fabric is dried, and the temperature can be 110-130°C, such as 120°C, and the time can be 25-35min, such as 30min.

[0050] In the present invention, after the physical treatment, the weight change rate Δwt1 of the aramid fiber or aramid fabric is controlled to be ≥5wt%, Δwt1 is preferably 5-6wt%, for example 5.5wt%, wherein the weight change rate Δwt1 is calculated as follows: Δwt1 = (m1-m2) / m1×100%, wherein m1 is the mass of the untreated aramid fiber or aramid fabric, and m2 is the mass of the aramid fiber or aramid fabric after the first physical treatment (first high-temperature solution ultrasonic treatment and drying, then ethanol ultrasonic treatment and drying). The weight change rate Δwt1 can be controlled by controlling the time of the high-temperature solution ultrasonic treatment and the ethanol ultrasonic treatment. Controlling the weight change rate Δwt1 within the aforementioned range is beneficial to improving the wettability and bonding phase between the aramid fiber and the epoxy resin.

[0051] In the present invention, sizing can be performed by coating a sizing agent onto aramid fiber or aramid fabric, or by dipping the aramid fiber or aramid fabric into a sizing agent for a period of time. In the present invention, the sizing agent is an aqueous solution containing m-phenylenedimethyl isocyanate type heat-tough polyurethane and an optional coupling agent. In a preferred embodiment, the present invention adopts a vacuum assistant resin infusion (VARI) mass production continuous process to apply the sizing agent onto aramid fiber or aramid fabric by continuous glue coating. The VARI process is a known method for impregnating fibers and fabrics thereof by utilizing the flow and penetration of resin under vacuum pressure. Sizing using the VARI process can effectively improve sizing efficiency and is conducive to performance improvement.

[0052] In the present invention, the m-xylylene isocyanate type thermally tough polyurethane refers to a compound having a structure shown in Formula I:

[0053]

[0054] In Formula I, R is a linker group containing one or more groups selected from the group consisting of an ether bond (—O—), an ester group (—COO—) and a hydroxyl group (—OH).

[0055] The isocyanate-based thermoplastic polyurethane suitable for use in the present invention may be polyester-based or polyether-based, i.e., R may contain an ester group (-COO-) or an ether bond (-O-), and may be aliphatic or aromatic, i.e., R may contain no aromatic group or contain an aromatic group. Examples of aliphatic polyester isocyanate-based thermoplastic polyurethanes include the isocyanate-based thermoplastic polyurethanes contained in Sancure 1601. Examples of aliphatic polyether isocyanate-based thermoplastic polyurethanes include the isocyanate-based thermoplastic polyurethanes contained in Sancure 2026C. Examples of aromatic polyether isocyanate-based thermoplastic polyurethanes include the isocyanate-based thermoplastic polyurethanes contained in Sancure 20066. In some embodiments, the meta-xylylene isocyanate-based heat-tough polyurethane used in the present invention is a meta-xylylene isocyanate-based heat-tough polyurethane contained in one or more meta-xylylene isocyanate-based heat-tough polyurethane emulsions selected from Sancure 1601, Sancure 2026C and Sancure 20066.

[0056] The meta-phenylenediisocyanate type thermo-tough polyurethane can be provided in the form of an emulsion. In the present invention, the meta-phenylenediisocyanate type thermo-tough polyurethane emulsion refers to an aqueous dispersion system containing meta-phenylenediisocyanate type thermo-tough polyurethane. The solid content suitable for the meta-phenylenediisocyanate type thermo-tough polyurethane emulsion is preferably 40±5%, the viscosity at room temperature is preferably 60±10cps, the pH is preferably 7.5±0.5, and the surface tension is preferably 46.7±5dynes / cm. The meta-phenylenediisocyanate type thermo-tough polyurethane emulsion that meets the aforementioned preferred requirements includes but is not limited to Sancure1601, Sancure2026C and Sancure20066.

[0057] In the present invention, the sizing agent optionally or preferably contains a coupling agent. The coupling agent suitable for the present invention includes one or more selected from aziridine crosslinking agents and epoxy-terminated polyether type silicone coupling agents.

[0058] In the present invention, the aziridine crosslinking agent refers to a compound containing multiple aziridine ring end groups. The aziridine crosslinking agent suitable for the present invention can be a trifunctional aziridine crosslinking agent, such as trimethylolpropane-tris (3-aziridine propionate) (structural formula: ), trimethylolpropane-tris[3-(2-methylaziridinyl)propionate], etc. Examples of trimethylolpropane-tris(3-aziridinylpropionate) include CX100.

[0059] In the present invention, the epoxy-terminated polyether-type silane coupling agent refers to a silane coupling agent having an epoxy terminal group and an ether bond. The epoxy-terminated polyether-type silane coupling agent suitable for the present invention includes but is not limited to glycidyloxypropyltrimethoxysilane, glycidyloxypropyltriethoxysilane, and the like.

[0060] In a preferred embodiment, the sizing agent comprises an epoxy-terminated polyether-type silicone coupling agent. The epoxy-terminated polyether-type silicone coupling agent has a synergistic effect with the meta-xylylene isocyanate-type thermally tough polyurethane, which can further improve the wettability and adhesion between the aramid fiber and the epoxy resin.

[0061] In some embodiments, the epoxy-terminated polyether-type siloxy coupling agent used in the present invention is γ-glycidyloxypropyltrimethoxysilane, which has a structure shown in Formula II:

[0062]

[0063] Examples of γ-glycidyloxypropyltrimethoxysilane include SCA E87M. SCA E87M is a colorless, clear, transparent liquid having a viscosity of 250 cps and a pH of 10.5, is slightly soluble in water, and undergoes hydrolysis.

[0064] The epoxy-terminated polyether-type silicone coupling agent will undergo hydrolysis, so when the epoxy-terminated polyether-type silicone coupling agent and the meta-phenylenedimethyl isocyanate-type thermally tough polyurethane emulsion are formulated into a sizing agent, they must be prepared immediately before use.

[0065] In the present invention, the content of the isocyanate-type thermo-tough polyurethane emulsion in the sizing agent can be 5wt%-15wt%, preferably 8wt%-13wt%, such as 9wt%, 10wt%, 11wt%, 12wt%. The content of isocyanate-type thermo-tough polyurethane in the sizing agent can be 2wt%-6wt%, preferably 3wt%-5wt%, such as 3.5wt%, 4wt%, 4.5wt%. When the sizing agent contains a coupling agent, the mass of the coupling agent in the sizing agent can be 1-10% of the mass of the isocyanate-type thermo-tough polyurethane emulsion, preferably 2-5%, such as 3%, 4%; the mass of the coupling agent in the sizing agent can be 2.5-25% of the mass of the isocyanate-type thermo-tough polyurethane, preferably 5-12.5%, such as 7.5%, 10%.

[0066] In some embodiments, the coupling agent and the isocyanate-based heat-resistant polyurethane emulsion are diluted with water by 8-12 times, for example, 9 times, 10 times, and 11 times, respectively, to obtain an oxygen coupling agent dilution and an isocyanate-based heat-resistant polyurethane emulsion dilution, and then the coupling agent dilution and the isocyanate-based heat-resistant polyurethane emulsion dilution are mixed uniformly in a certain proportion to obtain a sizing agent. The mass of the coupling agent dilution is 1-10% of the mass of the isocyanate-based heat-resistant polyurethane emulsion dilution, preferably 2-5%, for example 3%, 4%.

[0067] In some embodiments, the sizing agent comprises or consists of a meta-xylylene diisocyanate type heat-tough polyurethane emulsion, water, and an optional coupling agent.

[0068] In some embodiments, the sizing agent is applied to the aramid fiber or aramid fabric treated by the first physical method by single-sided brushing.

[0069] After the sizing agent is applied to the aramid fiber or aramid fabric, it will penetrate the surface of the material. After the sizing is completed (i.e., after the sizing agent is penetrated), it is dried at a temperature of 110-130° C., such as 120° C., for 25-35 minutes, such as 30 minutes.

[0070] In the present invention, the sizing rate Δwt2 is controlled to be 1-5wt%, preferably 1-3wt%, for example 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.5wt%, wherein the calculation formula of the sizing rate Δwt2 is: Δwt2 = (m3-m2) / m2×100%, wherein m2 is the mass of the aramid fiber or aramid fabric after the first step of physical treatment (ultrasonic treatment and drying of high temperature solution, ultrasonic treatment and drying of ethanol), and m3 is the mass of the aramid fiber or aramid fabric after the second step of chemical treatment (sizing and drying). The sizing rate Δwt2 can be controlled by controlling the amount of sizing agent applied or the impregnation time. Controlling the sizing rate Δwt2 within the aforementioned range is beneficial to improving the wettability and bonding phase between the aramid fiber and the epoxy resin.

[0071] After the aramid fiber or aramid fabric is treated by the method of the present invention, the surface of the aramid fiber or aramid fabric is free of oil agent, and the surface is bound with meta-phenylenedimethyl isocyanate type thermal toughness polyurethane and an optional coupling agent. Therefore, the present invention includes such aramid fiber or aramid fabric having no oil agent on the surface and having meta-phenylenedimethyl isocyanate type thermal toughness polyurethane and an optional coupling agent bound with the surface.

[0072] In the present invention, aramid fibers and aramid fabrics (e.g., aramid woven fabrics, aramid nonwoven fabrics) treated by physical and chemical methods and epoxy resins can be made into aramid epoxy resin composite materials such as laminates by vacuum bag hot pressing or the like. The preparation method of aramid epoxy resin composite materials such as laminates is known in the art. For example, vacuum bag hot pressing is used, the vacuum bag holding time can be 8-12 minutes, for example, 10 minutes, the vacuum loss can be controlled to be less than 0.2 kpa, the curing temperature can be 110-130°C, for example, 120°C, and the curing time can be 1.5-2.5 hours, for example, 2 hours. The number of layers of aramid fabrics in the aramid epoxy resin laminate can be 5-50 layers, for example, 10 layers, 20 layers, 30 layers, 40 layers, and the mass fraction of epoxy resin in the laminate can be 20%-50%, for example, 35±5%.

[0073] The aramid epoxy resin composite material prepared by the present invention, such as an aramid epoxy resin laminate, can be applied to a lower box body of a lithium ion battery or a lithium ion battery pack battery box.

[0074] Therefore, the present invention also includes the aramid epoxy resin composite material described in the text and a battery box or a battery box lower body of a lithium-ion battery or a lithium-ion battery pack.

[0075] The present invention has the following advantages and beneficial effects:

[0076] (1) The present invention combines physical and chemical methods to treat aramid fibers. The physical method uses a high-temperature solution ultrasonic method, which is gentle and simple and reduces damage to the fibers. The chemical method uses a chemical sizing process to increase the chemical bonding sites between the aramid fiber surface and the epoxy resin, thereby improving the wettability of the epoxy resin to the fiber, thereby fundamentally improving the adhesion between the aramid fiber and the epoxy resin.

[0077] (2) The present invention adopts a high-temperature solution ultrasonic method to efficiently remove the oil on the surface of the aramid woven fabric, with high removal efficiency and simple operation; the subsequent chemical sizing ensures that even if the oil is removed, the aramid fiber still has good processability and will not wear out.

[0078] (3) The chemical sizing process of the present invention strictly controls the content of the sizing agent, effectively increasing the bonding performance of the aramid fiber and the epoxy resin.

[0079] (4) The aramid fiber treated by the method of the present invention is used to prepare an aramid epoxy resin composite material, and the impregnation time is greatly shortened, the processing efficiency can be improved by about 65%-80%, and the bonding performance can be improved by more than 50%.

[0080] (5) The prior art has high requirements for equipment, high investment, difficult process, complex treatment method, and certain damage to the fiber, which is not conducive to large-scale industrialization and industrial promotion. The advantages of the present invention are that the treatment method is gentle and simple, the operation method is efficient and easy, the requirements for equipment and personnel are not high, but the treatment effect is excellent. The aramid woven fabric modified by the method of the present invention greatly improves the wettability with epoxy resin, and the interlaminar shear strength of the processed aramid epoxy composite laminate is greatly improved, which completely solves the problem of poor adhesion of aramid fibers.

[0081] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0082] The aramid fiber used in the examples and comparative examples is para-aramid fiber produced by Zhonghua Gaoxian, with a model of SF2800, a fineness of 1000D, a tensile strength greater than 19 cN / dtex, and an elongation of 3.5±0.2%.

[0083] The m-phenylenediisocyanate-based thermally tough polyurethane emulsion, Sancure 815 polyurethane emulsion, and epoxy-terminated polyether-based silicone coupling agent used in the examples and comparative examples were purchased from Lubrizol.

[0084] Examples 1-3

[0085] The following methods are used to treat aramid woven fabrics to improve their wettability and adhesion to epoxy resin:

[0086] (1) 220g / m2 processed from 1000D aramid fiber 2 Woven fabrics undergo the first step of processing:

[0087] First, high-temperature solution ultrasonic treatment and drying are performed: the aramid woven fabric is ultrasonically treated in a washing solution, the washing solution is an aqueous solution containing 10wt% sodium dodecylbenzene sulfonate and 10wt% sodium fatty alcohol ether sulfate, the pH is adjusted to 8.5 with ammonia water, the solution temperature is 80°C, the ultrasonic frequency is 80KHz, the treatment time is 30min, and the ultrasonic drying is performed after drying, the drying temperature is 120°C, and the drying temperature is 30min;

[0088] Then, ultrasonic treatment and drying in ethanol were performed: the aramid woven fabric treated with ultrasonic treatment in high temperature solution was ultrasonicated in anhydrous ethanol, the ultrasonic frequency was 50KHz, the treatment time was 10min, the treatment temperature was room temperature, and drying was performed after ultrasonication, the drying temperature was 120℃, and the drying temperature was 30min;

[0089] The weight change of aramid woven fabric after the first step treatment was 5.5%;

[0090] (2) Use different chemical sizing agents for the second step:

[0091] Wet sizing and drying: using VARI mass production continuous process to apply the sizing agent to the aramid woven fabric treated in the first step by continuous gluing, wherein the sizing agent used in Example 1 is Sancure1601, a thermo-tough polyurethane emulsion of m-phenylenedimethyl isocyanate diluted 10 times with deionized water, the sizing agent used in Example 2 is Sancure2026C, a thermo-tough polyurethane emulsion of m-phenylenedimethyl isocyanate diluted 10 times with deionized water, and the sizing agent used in Example 3 is Sancure20066, a thermo-tough polyurethane emulsion of m-phenylenedimethyl isocyanate diluted 10 times with deionized water; drying after sizing, the drying temperature is 120°C, and the drying temperature is 30min;

[0092] The sizing rate in Examples 1-3 is 1.2%.

[0093] Test Example 1

[0094] The aramid woven fabrics treated in Examples 1-3 and MERICAN 3315A / 3315B flame-retardant liquid epoxy resin were used to prepare laminates by vacuum bag hot pressing: 20 layers of aramid woven fabrics were stacked and laid, bagging and air tightness inspection were completed, vacuum was evacuated and pressure was maintained for 10 minutes, and the vacuum loss was less than 0.2kpa, and then epoxy resin was introduced. The resin temperature was room temperature 25°C, and the content of epoxy resin was controlled to be 35% of the total weight of epoxy resin and aramid woven fabric. The impregnation time of different aramid woven fabrics was recorded, and after complete impregnation, they were cured in an oven at a curing temperature of 120°C and a curing time of 2h to complete the preparation of aramid fiber epoxy resin laminate composite materials. The impregnation time refers to the time after the epoxy resin is introduced, when the epoxy resin completely penetrates and wets the aramid fiber. The impregnation time of aramid woven fabrics and epoxy resins is shown in Table 1.

[0095] According to ASTM D2344 standard test method for short beam shear strength of polymer matrix composite materials and their laminates, the sample preparation and interlaminar shear strength and bending load tests of aramid fiber epoxy resin laminate composite materials were carried out. The sample specification was 24*8mm. The results are shown in Table 1.

[0096] Table 1: Wetting time of aramid woven fabric and epoxy resin and interlaminar shear strength and bending load of composite materials

[0097]

[0098]

[0099] Embodiment 4-6

[0100] The following methods are used to treat aramid woven fabrics to improve their wettability and adhesion to epoxy resin:

[0101] (1) 220g / m2 processed from 1000D aramid fiber 2 Woven fabrics undergo the first step of processing:

[0102] First, high-temperature solution ultrasonic treatment and drying are performed: the aramid woven fabric is ultrasonically treated in a washing solution, the washing solution is an aqueous solution containing 10wt% sodium dodecylbenzene sulfonate and 10wt% sodium fatty alcohol ether sulfate, the pH is adjusted to 8.5 with ammonia water, the solution temperature is 80°C, the ultrasonic frequency is 80KHz, the treatment time is 30min, and the ultrasonic drying is performed after drying, the drying temperature is 120°C, and the drying temperature is 30min;

[0103] Then, ultrasonic treatment and drying in ethanol were performed: the aramid woven fabric treated with ultrasonic treatment in high temperature solution was ultrasonicated in anhydrous ethanol, the ultrasonic frequency was 50KHz, the treatment time was 10min, the treatment temperature was room temperature, and drying was performed after ultrasonication, the drying temperature was 120℃, and the drying temperature was 30min;

[0104] (2) Use different chemical sizing agents for the second step:

[0105] Wet sizing and drying: The sizing agent is applied to the aramid fabric treated in the first step by continuous gluing using the VARI mass production continuous process, wherein the sizing agent used in Example 4 is a mixed solution of m-xylene diisocyanate type thermoflexible polyurethane emulsion Sancure1601 diluted 10 times with deionized water and aziridine crosslinker CX-100 diluted 10 times with deionized water, and the sizing agent used in Example 5 is a mixed solution of m-xylene diisocyanate type thermoflexible polyurethane emulsion Sancure2026C diluted 10 times with deionized water and A mixed solution of aziridine crosslinker CX-100 diluted 10 times with deionized water. The sizing agent used in Example 6 is a mixed solution of m-phenylenedimethyl isocyanate type heat-resistant polyurethane emulsion Sancure20066 diluted 10 times with deionized water and aziridine crosslinker CX-100 diluted 10 times with deionized water. The amount of aziridine crosslinker dilution in the sizing agents of Examples 4-6 is 2wt% of the m-phenylenedimethyl isocyanate type heat-resistant polyurethane emulsion dilution. After sizing, drying is performed at a drying temperature of 120°C for 30 minutes.

[0106] The sizing rate in Examples 4-6 is 1.2%.

[0107] Test Example 2

[0108] The aramid woven fabrics treated in Examples 4-6 and MERICAN 3315A / 3315B flame-retardant liquid epoxy resin were used to prepare laminates by vacuum bag hot pressing: 20 layers of aramid woven fabrics were stacked and laid, and the bagging and air tightness inspection were completed. The vacuum was evacuated and the pressure was maintained for 10 minutes, and the vacuum loss was less than 0.2kpa. Then, the epoxy resin was introduced. The resin temperature was room temperature 25°C. The content of epoxy resin was controlled to be 35% of the total weight of epoxy resin and aramid woven fabric. The impregnation time of different aramid woven fabrics was recorded. After complete impregnation, they were cured in an oven at a curing temperature of 120°C and a curing time of 2h to complete the preparation of aramid fiber epoxy resin laminate composite materials. The impregnation time refers to the time after the epoxy resin is introduced, when the epoxy resin completely impregnates and wets the aramid fiber. The impregnation time of aramid woven fabrics and epoxy resin is shown in Table 2.

[0109] According to ASTM D2344 standard test method for short beam shear strength of polymer matrix composites and their laminates, the sample preparation and interlaminar shear strength and bending load tests of aramid fiber epoxy resin laminate composite materials were carried out. The sample specification was 24*8mm. The results are shown in Table 2.

[0110] Table 2: Wetting time of aramid woven fabric and epoxy resin and interlaminar shear strength and bending load of composite materials

[0111]

[0112] Embodiment 7-9

[0113] The following methods are used to treat aramid woven fabrics to improve their wettability and adhesion to epoxy resin:

[0114] (1) 220g / m2 processed from 1000D aramid fiber 2 Woven fabrics undergo the first step of processing:

[0115] First, high-temperature solution ultrasonic treatment is performed: the aramid woven fabric is ultrasonically treated in a washing solution, the washing solution is an aqueous solution containing 10wt% sodium dodecylbenzene sulfonate and 10wt% sodium fatty alcohol ether sulfate, the pH is adjusted to 8.5 with ammonia water, the solution temperature is 80°C, the ultrasonic frequency is 80KHz, the treatment time is 30min, and the ultrasonic drying is performed after drying, the drying temperature is 120°C, and the drying temperature is 30min;

[0116] Then, ultrasonic treatment and drying in ethanol were performed: the aramid woven fabric treated with ultrasonic treatment in high temperature solution was ultrasonicated in anhydrous ethanol, the ultrasonic frequency was 50KHz, the treatment time was 10min, the treatment temperature was room temperature, and drying was performed after ultrasonication, the drying temperature was 120℃, and the drying temperature was 30min;

[0117] (2) Use different chemical sizing agents for the second step:

[0118] Wet sizing and drying: The sizing agent is applied to the aramid fabric treated in the first step by continuous gluing using a VARI mass production continuous process, wherein the sizing agent used in Example 7 is a mixed solution of a meta-phenylenedimethyl isocyanate-type heat-tough polyurethane emulsion Sancure1601 diluted 10 times with deionized water and a terminal epoxy polyether type siloxane coupling agent SCA E87M diluted 10 times with deionized water, the sizing agent used in Example 8 is a mixed solution of a meta-phenylenedimethyl isocyanate-type heat-tough polyurethane emulsion Sancure2026C diluted 10 times with deionized water and a terminal epoxy polyether type siloxane coupling agent SCA E87M diluted 10 times with deionized water, and the sizing agent used in Example 9 is a meta-phenylenedimethyl isocyanate-type heat-tough polyurethane emulsion Sancure20066 diluted 10 times with deionized water and a terminal epoxy polyether type siloxane coupling agent SCA E87M diluted 10 times with deionized water. The mixed solution of E87M, the addition amount of the end epoxy polyether type silicone coupling agent dilution in the sizing agent of Examples 7-9 is 2wt% of the dilution of the meta-phenylenedimethyl isocyanate type thermal toughness polyurethane emulsion; drying after sizing, the drying temperature is 120°C, and the drying temperature is 30min;

[0119] The sizing rate in Examples 7-9 was 1.2%.

[0120] Test Example 3

[0121] The aramid woven fabrics treated in Examples 7-9 were prepared with MERICAN 3315A / 3315B flame-retardant liquid epoxy resin by vacuum bag hot pressing: 20 layers of aramid woven fabrics were stacked and laid, bagging and air tightness inspection were completed, vacuum was evacuated and pressure maintained for 10 minutes, and the vacuum loss was less than 0.2kpa, and then epoxy resin was introduced. The resin temperature was room temperature 25°C, and the content of epoxy resin was controlled to be 35% of the total weight of epoxy resin and aramid woven fabric. The impregnation time of different aramid woven fabrics was recorded, and after complete impregnation, they were cured in an oven at a curing temperature of 120°C and a curing time of 2h to complete the preparation of aramid fiber epoxy resin laminate composite material. The impregnation time refers to the time after the epoxy resin is introduced, when the epoxy resin completely impregnates and wets the aramid fiber. The impregnation time of aramid woven fabric and epoxy resin is shown in Table 3.

[0122] According to ASTM D2344 standard test method for short beam shear strength of polymer matrix composites and their laminates, the sample preparation and interlaminar shear strength and bending load tests of aramid fiber epoxy resin laminate composite materials were carried out. The sample specification was 24*8mm. The results are shown in Table 3.

[0123] Table 3: Wetting time of aramid woven fabric and epoxy resin and interlaminar shear strength and bending load of composite materials

[0124]

[0125] Comparative Example 1

[0126] 1000D aramid fiber 220g / m 2 Woven fabrics are not treated in any way.

[0127] Comparative Example 2

[0128] 1000D aramid fiber 220g / m 2 The woven fabric was not subjected to the first step treatment, but was directly subjected to the second step treatment using the chemical sizing agent in Example 9, with a sizing rate of 1.2%.

[0129] Comparative Example 3

[0130] 1000D aramid fiber 220g / m 2 The woven fabric was subjected to the first step treatment according to Example 1, without the second step chemical sizing treatment.

[0131] Test Example 4

[0132] The aramid woven fabrics treated in Comparative Examples 1-3 and MERICAN 3315A / 3315B flame-retardant liquid epoxy resin were used to prepare laminates by vacuum bag hot pressing: 20 layers of aramid woven fabrics were stacked and laid, bagging and air tightness inspection were completed, vacuum was evacuated and pressure was maintained for 10 minutes, and the vacuum loss was less than 0.2kpa, and then epoxy resin was introduced. The resin temperature was room temperature 25°C, and the content of epoxy resin was controlled to be 35% of the total weight of epoxy resin and aramid woven fabric. The impregnation time of different aramid woven fabrics was recorded, and after complete impregnation, they were cured in an oven at a curing temperature of 120°C and a curing time of 2h to complete the preparation of aramid fiber epoxy resin laminate composite materials. The impregnation time refers to the time after the epoxy resin is introduced, when the epoxy resin completely impregnates and wets the aramid fiber. The impregnation time of aramid woven fabrics and epoxy resin is shown in Table 4.

[0133] According to ASTM D2344 standard test method for short beam shear strength of polymer matrix composites and their laminates, the sample preparation and interlaminar shear strength and bending load tests of aramid fiber epoxy resin laminate composite materials were carried out. The sample specification was 24*8mm. The results are shown in Table 4.

[0134] Table 4: Wetting time of aramid woven fabric and epoxy resin and interlaminar shear strength and bending load of composite materials

[0135]

[0136] The test results of Examples 1-9 and Comparative Examples 1-3 show that the wettability and adhesion of the aramid woven fabric and the epoxy resin after the high-temperature solution ultrasonic treatment and chemical sizing treatment are greatly improved. The improvement of wettability is reflected in the shortening of the wetting time. The improvement of adhesion is reflected in the improvement of interlaminar shear strength and bending load. Through the VARI continuous mass production process, the use of m-phenylenedimethyl isocyanate-type thermal toughness polyurethane and terminal epoxy polyether-type silicone coupling agent can greatly improve the processing efficiency and greatly improve the adhesion of aramid fiber to epoxy resin. It can be seen that the present invention fundamentally solves the defects of poor wettability and poor adhesion of aramid fiber to epoxy resin, can effectively promote the use of aramid fiber in the field of composite materials, and give full play to the many advantages of aramid fiber such as high strength, high modulus, high dimensional stability, high temperature resistance and chemical corrosion resistance.

[0137] Comparative Example 4

[0138] This comparative example uses a polyurethane emulsion with the brand name Sancure815, in which the main structure of the polyurethane is consistent with the meta-phenylenediisocyanate type thermal toughness polyurethane, but the end group on the benzene ring is a hydroxyl group, rather than the isocyanate end group contained in the polyurethane in the polyurethane emulsions with the brands Sancure1601, Sancure2026C and Sancure20066.

[0139] Aramid woven fabrics are treated by the following methods:

[0140] (1) 220g / m2 processed from 1000D aramid fiber 2 Woven fabrics undergo the first step of processing:

[0141] First, high-temperature solution ultrasonic treatment is performed: the aramid woven fabric is ultrasonically treated in a washing solution, the washing solution is an aqueous solution containing 10wt% sodium dodecylbenzene sulfonate and 10wt% sodium fatty alcohol ether sulfate, the pH is adjusted to 8.5 with ammonia water, the solution temperature is 80°C, the ultrasonic frequency is 80KHz, the treatment time is 30min, and the ultrasonic drying is performed after drying, the drying temperature is 120°C, and the drying temperature is 30min;

[0142] Then, ultrasonic treatment and drying in ethanol were performed: the aramid woven fabric treated with ultrasonic treatment in high temperature solution was ultrasonicated in anhydrous ethanol, the ultrasonic frequency was 50KHz, the treatment time was 10min, the treatment temperature was room temperature, and drying was performed after ultrasonication, the drying temperature was 120℃, and the drying temperature was 30min;

[0143] (2) Use different chemical sizing agents for the second step:

[0144] Wet sizing and drying are performed, and the sizing agent is applied to the aramid fabric treated in the first step by continuous gluing using a VARI mass production continuous process. The sizing agent used is a mixed solution of a polyurethane emulsion Sancure815 diluted 10 times with deionized water and a terminal epoxy polyether type silicone coupling agent SCA E87M diluted 10 times with deionized water. The amount of the terminal epoxy polyether type silicone coupling agent diluent added is 2wt% of the Sancure815 polyurethane emulsion diluent. The fabric is dried after sizing at a temperature of 120°C for 30 minutes.

[0145] In Comparative Example 4, the sizing rate is 1.2%.

[0146] Test Example 5

[0147] The aramid woven fabric treated in Comparative Example 4 and MERICAN 3315A / 3315B flame-retardant liquid epoxy resin were used to prepare laminates by vacuum bag hot pressing: 20 layers of aramid woven fabrics were stacked and laid, bagging and air tightness inspection were completed, vacuum was evacuated and pressure was maintained for 10 minutes, and the vacuum loss was less than 0.2kpa, and then epoxy resin was introduced. The resin temperature was room temperature 25°C, and the content of epoxy resin was controlled to be 35% of the total weight of epoxy resin and aramid woven fabric. The impregnation time of aramid woven fabric was recorded, and after complete impregnation, it was cured in an oven at a curing temperature of 120°C and a curing time of 2h to complete the preparation of aramid fiber epoxy resin laminate composite material. The impregnation time refers to the time after the epoxy resin is introduced, when the epoxy resin completely impregnates and wets the aramid fiber. The impregnation time of aramid woven fabric and epoxy resin is shown in Table 5.

[0148] According to ASTM D2344 standard test method for short beam shear strength of polymer matrix composites and their laminates, the sample preparation and interlaminar shear strength and bending load tests of aramid fiber epoxy resin laminate composite materials were carried out. The sample specification was 24*8mm. The results are shown in Table 5.

[0149] Table 5: Wetting time of aramid woven fabric and epoxy resin and interlaminar shear strength and bending load of composite materials

[0150]

[0151] From the results in Table 5, it can be seen that the test data of Comparative Example 3 and Comparative Example 4 are close. The experimental results of Examples 7-9 are obviously better than those of Comparative Example 4, indicating that the polyurethane with terminal isocyanate group (such as Sancure1601, Sancure2026C and Sancure20066) used in the present invention and the epoxy-terminated polyether-type silicone coupling agent (such as SCA E87M) have a significant synergistic effect in improving the wettability of epoxy resin on aramid and the adhesion between aramid and epoxy resin, which is the most important innovation of the present invention.

Claims

1. A method for improving the wettability and / or adhesion of aramid fiber or aramid fabric with epoxy resin or a method for treating aramid fiber or aramid fabric, characterized in that: The method comprises the following steps: (1) physical treatment, comprising sequentially subjecting the aramid fiber or aramid fabric to high temperature solution ultrasonic treatment and ethanol ultrasonic treatment, wherein the high temperature solution ultrasonic treatment comprises ultrasonic treatment at a temperature above 60° C. using a washing solution, wherein the washing solution comprises sodium dodecylbenzene sulfonate and sodium fatty alcohol ether sulfate; (2) Chemical treatment, comprising sizing the aramid fiber or aramid fabric after physical treatment with a sizing agent, wherein the sizing agent comprises a m-phenylenediisocyanate-type thermoplastic polyurethane and an epoxy-terminated polyether-type silicone coupling agent, and the m-phenylenediisocyanate-type thermoplastic polyurethane contains an isocyanate group as a terminal group.

2. The method according to claim 1, characterized in that The physical treatment has one or more of the following characteristics: In the washing solution, the content of sodium dodecylbenzene sulfonate is 5-15wt%, and the content of sodium fatty alcohol ether sulfate is 5-15wt%; The pH of the washing solution is 8-9; In the ultrasonic treatment of the high temperature solution, the ultrasonic temperature is 70-90°C, the ultrasonic frequency is 60-100KHz, and the ultrasonic time is 20-40min; After the high temperature solution is ultrasonically treated, the aramid fiber or aramid fabric is dried, and then subjected to ethanol ultrasonic treatment; In the ethanol ultrasonic treatment, the ultrasonic temperature is 20-30° C., the ultrasonic frequency is 40-70 KHz, and the ultrasonic time is 8-12 min; After the ethanol ultrasonic treatment, the aramid fiber or aramid fabric is dried and then subjected to chemical treatment; After the physical treatment, the weight change rate of the aramid fiber or aramid fabric is ≥5wt%; The aramid fabric is aramid woven fabric, aramid knitted fabric or aramid non-woven fabric.

3. The method according to claim 1, characterized in that After the physical treatment, the weight change rate of the aramid fiber or aramid fabric is 5wt%-6wt%.

4. The method according to claim 1, characterized in that The isocyanate-based heat-resistant polyurethane is an isocyanate-based heat-resistant polyurethane contained in one or more isocyanate-based heat-resistant polyurethane emulsions selected from Sancure 1601, Sancure 2026C and Sancure 20066.

5. The method according to claim 1, characterized in that The epoxy-terminated polyether-type silicone coupling agent is glycidyloxypropyltrimethoxysilane and / or glycidyloxypropyltriethoxysilane.

6. The method according to claim 1, characterized in that The content of the m-xylylene isocyanate type heat-tough polyurethane in the sizing agent is 2wt%-6wt%.

7. The method according to claim 1, characterized in that The mass of the epoxy-terminated polyether-type silicone coupling agent in the sizing agent is 2.5-25% of the mass of the meta-xylylene isocyanate-type thermally tough polyurethane.

8. The method according to claim 1, characterized in that The sizing agent is prepared by using meta-xylylene isocyanate type heat-tough polyurethane emulsion.

9. The method according to claim 8, characterized in that The method has one or more of the following features: The solid content of the meta-xylylene isocyanate type thermally tough polyurethane emulsion is 40±5%; The room temperature viscosity of the meta-xylylene isocyanate type thermally tough polyurethane emulsion is 60±10cps; The pH of the meta-xylylene isocyanate type thermally tough polyurethane emulsion is 7.5±0.5; The surface tension of the meta-xylylene isocyanate type thermally tough polyurethane emulsion is 46.7±5dynes / cm; The m-xylylene isocyanate type thermally tough polyurethane emulsion is selected from one or more of Sancure1601, Sancure2026C and Sancure20066; The content of the meta-xylylene isocyanate type heat-tough polyurethane emulsion in the sizing agent is 5wt%-15wt%; The mass of the epoxy-terminated polyether-type silicone coupling agent in the sizing agent is 1-10% of the mass of the m-xylylene isocyanate-type thermally tough polyurethane emulsion.

10. The method according to claim 1, characterized in that In step (2), sizing is performed using a vacuum assisted resin introduction process.

11. The method according to claim 1, characterized in that In the chemical treatment, drying is performed after sizing is completed, and / or the sizing rate is controlled to be 1-5wt%.

12. The method according to claim 1, characterized in that In the chemical treatment, the sizing rate is controlled to be 1-3 wt %.

13. An aramid fiber or aramid fabric, characterized in that: The surface of the aramid fiber or the aramid fabric is free of oil agent, and is combined with isocyanate-type thermal toughness polyurethane and epoxy-terminated polyether-type silicone coupling agent on the surface. The isocyanate-type thermal toughness polyurethane contains isocyanate groups as terminal groups.

14. The aramid fiber or aramid fabric according to claim 13, characterized in that: The aramid fiber or aramid fabric is prepared by the method according to any one of claims 1 to 12.

15. An aramid epoxy resin composite material, characterized in that: The aramid epoxy resin composite material comprises the aramid fiber or aramid fabric according to claim 13 or 14 and epoxy resin.

16. The aramid epoxy resin composite material according to claim 15, characterized in that: The aramid epoxy resin composite material is an aramid epoxy resin laminate.

17. The aramid epoxy resin composite material according to claim 16, characterized in that: The aramid epoxy resin laminate comprises 5-50 layers of aramid fabrics, and the mass fraction of epoxy resin in the aramid epoxy resin laminate is 20%-50%.

18. The aramid epoxy resin composite material according to claim 17, characterized in that: The aramid epoxy resin laminate comprises 10 layers, 20 layers, 30 layers or 40 layers of aramid fabric.

19. A battery box or a lower box of a battery box for a lithium ion battery or a lithium ion battery pack, characterized in that: The battery box or the lower box of the battery box comprises the aramid epoxy resin composite material according to any one of claims 15-18.

Citation Information

Patent Citations

  • Reinforcing fibers and their use for concrete reinforcement

    CN103906717A